Pengaruh Dana Pihak Ketiga dan NPF Murabahah Terhadap Pembiayaan Murabahah Bank Umum Syariah - Cupian, Cupian; Noven, Sarah Annisa; Ramadhani, Muhammad Rizky (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to determine the effect of third-party funds, non-performing financing murabaha, and inflation on murabaha financing in Islamic banks. The data used in this research is monthly data from January 2015 to December 2021 obtained from Statistik Perbankan Syariah OJK and Bank Indonesia publication. Data is processed using multiple regression analysis to see the effect partially and simultaneously. The results of this research indicate that partially third-party funds have a significant positive effect, while the non-performing financing murabaha and the inflation rate has a significant negative effect on murabaha financing. All the factors simultaneously have significant effect.